Measurement of body temperature in postsurgical children: Comparisons of infrared nonskin contact digital thermometer, skin contact digital thermometer, and mercury in glass thermometer - Mitul Jasani; Alpa Jasani; Anirudh Shah; Amar Shah (Wolters Kluwer Medknow Publications, 2021)
Context: Postoperative fever is known to occur after all surgical procedures irrespective of the type of anesthesia. Thermometry devices that work without touching or disturbing the child seem to be appreciated more than the conventional skin contact thermometers. However, whether this technology is reliable to be adapted for routine pediatric surgical care is debatable. Aims: The aim of this study was to study the accuracy of infrared nonskin contact digital thermometer (IRT) compared to the skin contact digital thermometer (DT) and mercury in glass thermometer (MT). Settings and Design: A prospective cross-sectional study was done in postoperative patients at a pediatric surgical center over a period of 3 months. Subjects and Methods: The forehead temperature was recorded with IRT. This was followed by recording the temperature in one armpit by DT and the other armpit by MT. Readings were promptly documented. Statistical Analysis Used: A sample t-test was done which gave the P value and mean. Linear regression analysis was carried out to find correlation coefficients. Bland-Altman test was used to access the concordance between all readings. Results: We found a strong correlation between temperature readings taken by DT (mean = −0.03, r = 0.07, slope = −0.04) and IRT (mean = 0.89, r = 0.091, slope = −0.14). However, on comparison of results with the MT, there are wider limits of agreement with the IRT (−0.31-2.09) in comparison to DT (−0.66-0.59). Conclusion: Skin contact digital thermometer are more accurate and suitable for checking body temperature as compared to infrared nonskin contact digital thermometer in postoperative pediatric patients.